Factors enabling comprehensive maternal health services in the benefits package of emerging financing schemes: A crosssectional analysis from 1990 to 2014 - Vargas, Veronica; Ahmed, Sayem; Adams, Alayne M. (PLOS ONE, 2022)
This article was published in the PLOS ONE [© 2018 Vargas et al. This is an open access article distributed under the terms of the Creative Commons Attribution License ] and the definite version is available at: https://doi.org/10.1371/journal.pone.0201398 The Journal's website is at: https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0201398